Ultrasensitive method to quantify intracellular zidovudine mono‐, di‐ and triphosphate concentrations in peripheral blood mononuclear cells by liquid chromatography–tandem mass spectrometry. (5th May 2015) - Kinai, Ei; Gatanaga, Hiroyuki; Kikuchi, Yoshimi; Oka, Shinichi; Kato, Shingo
<x xml:space="preserve">Abstract</x> Although zidovudine (AZT) is not the preferred antiretroviral drug for adult HIV‐infected patients, it is still widely used in infants for both prevention of mother‐to‐infant HIV‐1 transmission and treatment of HIV‐infected children. However, it is difficult to measure intracellular concentrations of AZT metabolites in small blood samples due to their extremely low concentrations in peripheral blood mononuclear cells and interference by endogenous nucleotide triphosphates, residual plasma phosphates and electrolytes. We developed an ultrasensitive assay using liquid chromatography–tandem mass spectrometry (LC–MS/MS) for measurement of intracellular concentrations of zidovudine (AZT)‐monophosphate (AZT‐MP), ‐diphosphate (AZT‐DP) and ‐triphosphate (AZT‐TP). The high sensitivity was due to the improvement of peripheral blood mononuclear cells extraction for complete removal of plasma and electrolytes, alkalization of LC buffer and use of alkaline‐stable high performance liquid chromatography column and tetrabutylammonium hydroxide as the ion pair. Using this method, the lower limits of quantification of AZT, AZT‐MP, ‐DP and ‐TP were 6, 6, 10 and 10 fmol per sample, respectively. Accuracy ranged 89–115% and precision was lower than 15% in the quantification range of 6–6000 fmol/sample for plasma AZT and intracellular AZT‐MP and 10–10 000 fmol/sample for AZT‐DP and ‐TP. The validation parameters met the international requirements. Among nine AZT‐treated HIV‐infected adult patients, five had low AZT‐TP levels (<10 fmol/106 cells). Our assay has high sensitivity and is advantageous for evaluation of AZT phosphates in children and infants based on minimum blood sampling requirement. Copyright © 2015 John Wiley & Sons, Ltd.